2021
DOI: 10.18316/sdh.v9i1.6463
|View full text |Cite
|
Sign up to set email alerts
|

Erros na administração de medicamentos por cateteres gastrintestinais: revisão integrativa

Abstract: Objetivo: Sumarizar os erros existentes na administração de medicamentos por cateteres gastrintestinais.Método: Revisão integrativa de literatura, embasada em protocolo estabelecido e realizada em três bases de dados, sem recorte temporal, em qualquer idioma. Foram avaliados quanto ao nível de evidência e grau de recomendação e analisada por pares, situação em que as discordâncias foram resolvidas por consenso.Resultados: Selecionados sete artigos, nos quais cinco verificaram as práticas executadas na administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…15,16 In an analysis of the occurrence of incidents related to the use of probes in the ICU, 30 24.72% of the patients that were followed up suffered some incident related to the use of invasive devices, with 28.4% of these classified as mild harm to patients. In an integrative review, 31 all seven studies reported drug administration process deviations through gastrointestinal catheters, including lack of protocols for the preparation of drugs, drug-drug interactions, diet-drug interactions, and impermissible pharmaceutical form transformations. Such problems can lead to dose inaccuracy, contamination during drug handling, and chemical and physical incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In an analysis of the occurrence of incidents related to the use of probes in the ICU, 30 24.72% of the patients that were followed up suffered some incident related to the use of invasive devices, with 28.4% of these classified as mild harm to patients. In an integrative review, 31 all seven studies reported drug administration process deviations through gastrointestinal catheters, including lack of protocols for the preparation of drugs, drug-drug interactions, diet-drug interactions, and impermissible pharmaceutical form transformations. Such problems can lead to dose inaccuracy, contamination during drug handling, and chemical and physical incompatibilities.…”
Section: Discussionmentioning
confidence: 99%